03 EFISENSI TEKNIS USAHATANI PADI PADA LAHAN SKALA KECIL DI DESA AMPEKALE KECAMATAN BONTOA KABUPATEN MAROS - Jurnal Agribis; Muhammad Yusran; Abd. Asis Pata; Azisah Azisah (Jurnal Agribis, 2021)
One of the national foodstuffs strived to be provided throughout the year is rice because rice is a staple food consumed by almost all Indonesian people. Indonesia's rice consumption is the highest rice consumption in Asia. This research was conducted in the village of Ampekale, Bontoa District, Maros Regency. This location was chosen with consideration that has long been managing mulberry plants. There are two data used, namely: primary data, namely data obtained from observations through direct interviews and also through the help of questionnaire lists and secondary data, namely data obtained from agencies / institutions that are related or related to this research. The purpose of this study is: Knowing how much rice farming income on small scale land obtained by farmers in the village of Ampekale Bontoa District, Maros Regency. Analyzing the technical efficiency of rice farming on small scale land in the village of Ampekale Bontoa District, Maros Regency. Data was collected from survey results using a questionnaire and supplemented with field observations. The data that has been collected is then tabulated to get the real data used for analysis. The results of this research can be seen the amount of income obtained from rice farming on a small scale land in the village of Ampekale, Bontoa District, Maros Regency, on average, is Rp. 976,500.00. And rice farming on a small scale land in Ampekale Village, Bontoa District, Maros Regency is technically efficient.